Современные репродуктивные установки и их реализация - Злотников, А.Г. (Інститут демографії та соціальних досліджень НАН України, 2010)
Розглядається динаміка моделі народжуваності Білорусі на початку ХХІ сторіччя. Аналізуються структурні зміни народжуваності, тенденції народжуваності у розрізі основних вікових груп. Розкривається взаємозв’язок демографічних процесів Білорусі і активної державної демографічної політики. Прослідковується вплив сучасних демографічних концепцій та формування демографічної політики. Рассматривается динамика модели рождаемости Беларуси в начале XXI столетия. Анализируются структурные изменения рождаемости, тенденции рождаемости в разрезе основных возрастных групп. Раскрывается взаимосвязь демографических процессов Беларуси и активной государственной демографической политики. Прослеживается влияние современных демографических концепций на формирование демографической политики. Trends of the development of demographic situation in Belarus are characterized, which is so far has negative saldo of natural population growth. The dynamic of a model of birth in Belarus at the beginning of the 21-st century is investigated. Trends of reproductive behavior in Belarus, Ukraine and Russia are compared. The changes in the birth structure are analyzed. The analysis of the birth trends which corresponded to main age groups is given. It is noted, that growth of birth and new trends of reproductive behavior of some age groups have been occurred in the period of the global financial and economic crisis. The interconnection of demographic processes and active state demographic policy is discovered. The results of a sociological investigation in the framework of the regional demographic monitoring are given. The influence of modern demographic concepts on the formation of demographic policy is followed. The concepts of “family modernization” and “family crisis” are outlined.